Rapid assignment of malting barley varieties by matrix-assisted laser desorption-ionisation - Time-of-flight mass spectrometry - Šedo, Ondrej; Kořán, Michal; Jakešová, Michaela; Mikulíková, Renata; Boháč, Michal; Zdráhal, Zbyněk (Food chemistry, 2016)
A method for discriminating malting barley varieties based on direct matrix-assisted laser desorption-ionisation - time-of-flight mass spectrometry (MALDI-TOF MS) fingerprinting of proteins was developed. Signals corresponding to hordeins were obtained by simple mixing of powdered barley grain with a MALDI matrix solution containing 12.5mgmL(-1) of ferulic acid in an acetonitrile:water:formic acid 50:33:17 v/v/v mixture. Compared to previous attempts at MALDI-TOF mass spectrometric analysis of barley proteins, the extraction and fractionation steps were practically omitted, resulting in a significant reduction in analytical time and costs. The discriminatory power was examined on twenty malting barley varieties and the practicability of the method was tested on sixty barley samples acquired from Pilsner Urquell Brewery. The method is proposed as a rapid tool for variety assignment and purity determination of malting barley that may replace gel electrophoresis currently used for this purpose.
Keywords: MALDI-TOF MS; ječmen (rod); spektrometrie hmotnostní - ionizace laserem za účasti matrice; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Seedlings; gluteny; semenáček; Glutens; Barley; pivo; průmysl zpracování potravin; Hordeum; Malting; Proteins; Beer; Food-Processing Industry